Creación de una estrategia organizacional para el manejo de los residuos en el Resguardo Mosoco (2022)
In this work we present the current situation of the Mosoco Indigenous Reservation located in the department of Cauca with respect to garbage contamination that is reflected in the surroundings of this territory, offering a proposal for an organizational strategy to apply in the territory. , since reusing some materials is not part of the customs of the community that lives in this reservation, it is finally hoped that with the help of this strategy the contamination will go down and better care can be taken and a sense of belonging to mother earth.